Analysis of System Performance and Public Transportation Services of Trans Metro Dewata Bali Bus Rapid Transit (BRT) on Public Interest in Bali Province - Prihatini, Hikmah Tri; Mukhlis, Imam; Utomo, Sugeng Hadi Utomo (Journal of Applied Business, Taxation and Economics Research, 2024)
This study analyzes the influence of various factors (safety, security, comfort, affordability, equality, and order) on interest in using the Trans Metro Dewata Bali Bus Rapid Transit as a mode of public transportation in Bali. This research uses quantitative descriptive method with primary and secondary data collection and questionnaire distribution. Determination of the sample using the slovin formula with simple random sampling technique distributed to the Balinese people with a total of 100 samples. Testing the feasibility of the research instrument using the validity test calculated in the SPSS program. The results showed that the variables together had a significant influence on interest in using the system, with an R Square value of 0.368, indicating that 36.8% of the variance in interest could be explained by these factors. However, 63.2% of the variance is influenced by other variables not included in this study